COLLABORATION MANAGEMENT FOR SUBJECTS OF EDUCATIONAL ACTIVITY IN INFORMATION-EDUCATIONAL SPACE - Yury F. Telnov; Ekaterina V. Pavlova; Alla A. Protasova (Открытое образование (Москва), 2016)
This article presents a conception of collaboration of main actors in information-educational space, based on service level management process from the library of best practices ITIL, composition and procedure of information interchange between actors, responsibility of each actor, metrics and key performance indicators of each actor’s activity within educational service delivery.